A microbiological survey of automated biochemical machines. Issue 6 (June 1980) - Newsom, S W; Matthews, J
Abstract : The potential microbial hazards to laboratory personnel from operating three pieces of automated laboratory equipment have been tested using challenges of bacteria in serum or water. Aerosols did not seem to be a hazard, and the recommended disinfection procedures seemed quite adequate, although 2% aqueous activated glutaraldehyde is to be preferred to hypochlorite. The use of plastic gloves for protecting hands when changing rinse cups and pH electrodes is recommended.